Pengaruh Metode Sosiodrama Terhadap Hasil Belajar Siswa dalam Pembelajaran Sejarah di Masa Tatap Muka Terbatas - Sumaludin, M. Maman (Prabayaksa: Journal of History Education, 2022)
Less effective learning during the Covid-19 pandemic also affects student learning outcomes. So with the limited direct learning policy, it provides the opportunity for all parties to make maximum use of direct learning to improve student learning outcomes, one of which is through the sosiodrama method. This study aims to determine the effect of the sosiodrama method on student learning outcomes in history learning during the limited direct learning period. This research is a quasi experimental research with a non-equivalent group pretest-posttest design. Data collection techniques through observation, field notes, questionnaires, and documentation in the form of student learning outcomes. The population in this study is Class XI SMAN 4 Bandung with research samples Class XI IPS 1 as the experimental class and Class XI IPS 3 as the control class. This research was conducted in the even semester of the 2021/2022 academic year when limited direct learning was implemented. Data analysis used normality test, gain test, and descriptive data analysis. Based on the results of the analysis that there is an effect of the sosiodrama method on student learning outcomes in history learning during the limited direct learning period. The effectiveness is influenced by the learning method applied by the teacher is fun but still trains the cognitive, psychomotor, and affective aspects of students.